Modification of the Ladder Rung Walking Task—New Options for Analysis of Skilled Movements - Iwa Antonow-Schlorke; Julia Ehrhardt; Marcel Knieling (Stroke Research and Treatment)
Method sensitivity is critical for evaluation of poststroke motor function. Skilled walking was assessed in horizontal, upward, and downward rung ladder walking to compare the demands of the tasks and test sensitivity. The complete step sequence of a walk was subjected to analysis aimed at demonstrating the walking pattern, step sequence, step cycle, limb coordination, and limb interaction to complement the foot fault scoring system. Rats (males, n=10) underwent unilateral photothrombotic lesion of the motor cortex of the forelimb and hind limb areas. Locomotion was video recorded before the insult and at postischemic days 7 and 28. Analysis of walking was performed frame-by-frame. Walking along the rung ladder revealed different results that were dependent on ladder inclination. Horizontal walking was found to discriminate lesion-related motor deficits in forelimb, whereas downward walking demonstrates hind limb use most sensitively. A more frequent use of the impaired forelimb that possibly supported poststroke motor learning in rats was shown. The present study provides a novel system for a detailed analysis of the complete walking sequence and will help to provide a better understanding of how rats deal with motor impairments.